Intensity Of Gadget Usage And Sleep Quality On Teenager In Senior High School : Cross Sectional Study - Dyna Apriany; Dini Iryan; Rini Mulyati (Risenologi, 2021)
The trend of using gadgets at that age will cause gadget addiction and have an impact on health, one of which causes the quality of sleep to be disturbed. The adolescent population complained about sleep quality disturbances of 15-35%. The preliminary study conducted on adolescents at Senior High School found that some teenagers use gadgets as a medium of entertainment when they are bored without realizing it until they don't know the time, which causes poor sleep quality. This research to determine the relationship between the intensity of gadget use and the quality of sleep in teenager in Senior High School . The research design used an analytical survey with the cross sectional method. The research sample was 88 adolescents. Sampling using proportional stratified random sampling.The intensity of the use of gadgets were 42 respondents (47.7%), 76 respondents (86.4%) had poor sleep quality, and the results of statistical tests were obtained p-value (0.000) <? value (0.05). This means that there is a significant relationship between the intensity of gadget use and sleep quality in adolescents in Senior High School. Schools can work together with parents by providing counseling about good gadget use and considering other activities such as interactions or conversations with parents. So during the Covid-19 pandemic to balance the use of gadgets with other activities involving children. Because the impact of excessive use of gadgets will be bad for health.